Tailoring the monomers to overcome the shortcomings of current dental resin composites - review - Jingwei He; Lippo Lassila; Sufyan Garoushi; Pekka Vallittu (Medical Journals Sweden, 2023)
AbstractDental resin composites (DRCs) have become the first choice among different restorative materials for direct anterior and posterior restorations in the clinic. Though the properties of DRCs have been improved greatly in recent years, they still have several shortcomings, such as volumetric shrinkage and shrinkage stress, biofilm development, lack of radio-opacity for some specific DRCs, and estrogenicity, which need to be overcome. The resin matrix, composed of different monomers, constitutes the continuous phase and determine the performance of DRCs. Thus, the chemical structure of the monomers plays an important role in modifying the properties of DRCs. Numerous researchers have taken to design and develop novel monomers with specific functions for the purpose of fulfilling the needs in dentistry. In this review, the development of monomers in DRCs were highlighted, especially focusing on strategies aimed at reducing volumetric shrinkage and shrinkage stress, endowing bacteriocidal and antibacterial adhesion activities as well as protein-repelling activity, increasing radio-opacity, and replacing Bis-GMA. The influences of these novel monomers on the properties of DRCs were also discussed.